Physical properties and microstructural characterization of dental porcelains mixed with distilled water and modeling liquid - SINMAZIŞIK, GÜLDEN (ELSEVIER SCI LTD, 2006)
Objective. The aim of this study was to microstructurally characterize and to make comparisons of the physical properties of sintered dental porcelains prepared by mixing with distilled water and with their modeling liquid. Methods. Six commercial porcelain powders: IPS Classic (Ivoclar Vivadent AG, Schaan, Liechtenstein), IPS d.SIGN (Ivoclar Vivadent AG), IPS InLine (Ivoclar Vivadent AG), Vita VMK95 (Vita Zahnfabrk, Bad Sackingen, Germany), Vita OMEGA 900 (Vita) and Ceramco III (Ceramco-Dentsply, Burlington, NJ, USA) were used as starting powders. Following particle size and BET analyses of starting powders, each porcelain powder was mixed with distilled water and with its own modeling liquid. Disc specimens were sintered in accordance with each manufacturer's instructions. Specimens were characterized using X-ray diffraction (XRD), optical microscopy and SEM analysis and their physical properties such as bulk density, microhardness and biaxial flexural strength were determined. Results. The sintered dental porcelains premixed with modeling liquid had density, biaxial flexural strength and microhardness values slightly higher than those premixed with distilled water. Mixing with distilled water and modeling liquid caused statistically significant differences between the density values of Vita VMK 95 and microhardness values of IPS d.SIGN and IPS InLine. Characterization investigations (XRD and SEM) revealed the coexistence of the tetragonal leucite (1-3 mu m) and hexagonal fluorapatite crystals (0.4-1.2 mu m) in a feldspathic glassy matrix in the microstructure of IPS d.SIGN and only leucite crystals (3-6 mu m) in the microstructures of other porcelains. Significance. Mixing the porcelain powders with distilled water or modeling liquid prior to sintering has no effect on the resultant sintered crystalline microstructure. On the other hand, significant differences exist between the physical properties of some porcelains. (C) 2005 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: dental porcelain; modeling liquid; leucite; fluorapatite; microscopy; X-ray diffraction; flexural strength; STRENGTH; CERAMICS